2003
DOI: 10.1021/ic034281y
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl and Strontium Salt Solvation in Room-Temperature Ionic Liquids. A Molecular Dynamics Investigation

Abstract: Using molecular dynamics simulations, we compare the solvation of uranyl and strontium nitrates and uranyl chlorides in two room-temperature ionic liquids (ILs): [BMI][PF(6)] based on 1-butyl-3-methylimidazolium(+),PF(6)(-) and [EMI][TCA] based on 1-ethyl-3-methylimidazolium(+),AlCl(4)(-). Both dissociated M(2+),2NO(3)(-) and associated M(NO(3))(2) states of the salts are considered for the two cations, as well as the UO(2)Cl(2) and UO(2)Cl(4)(2)(-) uranyl complexes. In a [BMI][PF(6)] solution, the "naked" UO(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 54 publications
6
55
3
Order By: Relevance
“…The force field in AMBER framework was adopted in this work, and their abilities to simulate imidazolium ILs have been widely demonstrated 33–36, 41, 43, 44, 66–68, 79. Because of the addition of amino group, some new force field parameters need to be regressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The force field in AMBER framework was adopted in this work, and their abilities to simulate imidazolium ILs have been widely demonstrated 33–36, 41, 43, 44, 66–68, 79. Because of the addition of amino group, some new force field parameters need to be regressed.…”
Section: Resultsmentioning
confidence: 99%
“…A fundamental understanding of microstructure and interionic interaction in ILs is very valuable and necessary for understanding their properties, and further for rationalizing their designs. Molecular dynamics (MD) simulations have been used to study the microstructure of imidazolium ILs and predict their thermodynamic or dynamic properties 30–45. It has been concluded that their liquid phases are strongly organized through widely existing interionic hydrogen bonds and electrostatic interaction; anions prefer to organize around C2‐site on imidazolium ring and form strong hydrogen bonds with C2H, then followed by C4/C5sites, and have a weak interaction with alkyl side chains; such strong interionic interaction is responsible for the long‐range ordering in liquid, much higher vaporization heat and cohesive energy density that is consistent with their nonvolatile nature, and much lower ionic self‐diffusion coefficients (e.g., the predicted ionic self‐diffusion coefficients of imidazolium hexafluorophosphate and tetrafluoroborate ILs are around on the order of 10 −11 m 2 s −1 at room temperature,32, 33, 36, 45 which is about 2 order of magnitude lower than that of conventional molecule solvents, e.g., water is 2.3 × 10 −9 m 2 s −1 at 298 K and 1 atm46).…”
Section: Introductionmentioning
confidence: 99%
“…An important stabilizing force comes from the solvation of the UO 2 Cl 4 2-complex, which is embedded inside a cage of BMI + cations, featuring an onion-type alternation of solvent shells, also observed by MD studies of ions in ionic liquids. 30,31,72,73 Such a solvation pattern is a specific feature of ILs, compared to traditional molecular solvents whose dipoles orient with respect to the ionic solute. We also note that the UO 2 Cl 4 2-complex, when observed in nonaqueous solutions, has often quaternary ammonium, imidazolium, or phosphonium counterions, which are potential components of ILs, and therefore stabilize the complex in these media.…”
Section: Discussionmentioning
confidence: 99%
“…Chaumont and Wipff published detailed theoretical studies on this topic. [57][58][59][60][61][62] Their molecular dynamics calculations explicitly represent the solvent. Interesting conclusions were made on the basis of quantum mechanics and molecular dynamics calculations on trivalent lanthanide ions in the ionic liquids 1-butyl-3-methylimidazolium hexafluorophosphate, [C 4 .…”
Section: Solvationmentioning
confidence: 99%